Empowering Students Through Life Skill Development: A Case Study at Nurul Yaqin Islamic Boarding School - Zahra, Badri Aulia; Fadri, Zainal; Iswadi, Iswadi; Syafriwaldi, Syafriwaldi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
The main issue in this research is the implementation of life skill development for students at the Islamic boarding school in an effort to improve the quality of education, as well as the skills, talents, and interests of students, not only to fulfill religious needs but also to equip them with life skills needed in today’s competitive world. This research aims to understand the objectives of empowering students through life skill development and how these life skills are applied to students to prepare them for their future lives. The type of research used is field research, aimed at obtaining data on the issues being investigated. The data collection techniques used are interviews and documentation. The data management is conducted in a descriptive qualitative manner, followed by classification of specific aspects of the problem and presenting them in effective sentences. There is a lack of understanding and skills among students, especially those who are new or have not participated in life skill programs. In response, Nurul Yaqin Islamic Boarding School in Batipuah Ateh strives to provide facilities, motivation, guidance, and support to improve the quality of educators and students, helping them provide the best for the students and the community based on the foundation of life skill programs. The boarding school continuously prepares students and other members of the community to be ready for the demands of the global era by providing training, strengthening human resources, guidance, motivation, and awareness stages. The improvement in various fields undertaken by students, such as Qur'an family studies, computer training, tahfizh, qiratulkutub, and other activities, is aimed at enhancing achievements at various levels and improving the well-being of both individuals and the community, with a positive impact on the school and the wider society.